Rancang Bangun Sistem Pengendali Roda Kursi Otomatis dengan Sensor Flex Arduino Berbasis Mikrokontroler - Rieza Anara (Pusat Riset dan Inovasi Nasional, 2023)
A wheelchair is one of the equipment used by persons with physical disabilities in carrying out activities. Currently, there are still many wheelchairs that use human power to move them, so a wheelchair robot was made with motion control using flex sensor technology. This system uses two controllers as one master controller and one slave controller. Wheelchairs are often used by hospital patients as well as people with physical disabilities, most of whom still use manual systems. This device uses Bluetooth as a communication medium between two controllers. The Flex sensor is mounted in the user's hand as the master, and the controller in the wheelchair is a slave. So the researchers designed an automatic wheelchair simulator using flex sensor technology that helps facilitate wheelchair user activity by using curvature of the fingers. To move the walking wheelchair, use the command with the position of the fingers do the flexion and the position of the other fingers also do the flexion. In testing the wheelchair robot system, obtained the success rate of wheelchair movement with flex sensor commands of 83.3%.